Market Segmentation and Advertising Strategy in the Digital Age: A Qualitative Analysis of the Impact of Imperfect Targeting - Masitah, Siti; Ruslaini (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This study examines the impact of imperfect targeting on market segmentation and digital advertising strategies through a qualitative literature review. In the rapidly evolving digital era, consumer targeting accuracy has become a major challenge, especially with increasing data privacy regulations such as the GDPR. The study reveals that inaccurate targeting can reduce advertising effectiveness and intensify competition among companies to capture high-value consumers. Additionally, technological and regulatory barriers often hinder the achievement of optimal results in data-driven marketing strategies. However, technological innovations such as artificial intelligence (AI) and machine learning have the potential to improve targeting accuracy, thereby enhancing the outcomes of advertising campaigns. This research also highlights the need for balancing targeting efficiency with compliance to privacy regulations, as well as adopting more adaptive, value-based marketing approaches to foster long-term consumer relationships. These findings offer crucial insights for companies in devising advertising strategies within the dynamic and complex digital landscape.